The Effects of Fiscal Policieson the Economic Development of Women in the Middle East and North Africa - Laframboise, Nicole (IMF Working Papers; Working Paper, 2003)
Statistics indicate that the economic and social development of women in the Middle East and North Africa (MENA) compares unfavorably with most regions in the world. This paper assesses the influence of government expenditure and taxation policies on the economic and social welfare of women in the region. On the expenditure side, we test the explanatory power of public social spending in the determination of key female social indicators. We find that the relatively weak social outcomes for MENA women are not explained by the amount of government social spending, suggesting the answer lies in the efficiency and reach of present spending. With respect to taxation, the main issues in the literature on gender bias in taxation are highlighted and applied in a general manner to the MENA context. Some simple policy recommendations are suggested.